Coli surface antigens associated with enterotoxigenic Escherichia coli strains isolated from persons with traveler's diarrhea in Asia. - Serichantalergs, O (1997)
Enterotoxigenic Escherichia coli (ETEC) strains were isolated from travelers or military personnel who developed diarrhea after visiting Nepal or who were deployed to Thailand, Indonesia, or the Philippines. ETEC isolates were examined for colonization factor antigen (CFA). CFAs were identified on 59% (40 of 68) of the isolates examined. The lack of a detectable CFA on 41% (28 of 68) of the isolates is of concern for the development of an effective ETEC vaccine.